Dynamic behavior of soil-foundation-structure systems subjected to scour. Issue 152 (January 2022) - Antonopoulos, C.; Tubaldi, E.; Carbonari, S.; Gara, F.; Dezi, F.
Abstract: Earthquake and scouring are the leading causes of bridge failure worldwide, resulting not only in casualties and fatalities but also in enormous societal and economic losses. A great number of bridges in earthquake-prone countries cross rivers and have shallow foundations, which renders them highly vulnerable to the combined effects of earthquake and flood-induced scour. Thus, the research on the dynamic response of bridges with shallow foundations under scour and earthquake hazards is timely and imperative. This study investigates the problem through the development of a numerical model for evaluating the effect of scour on the impedance functions of a massless rigid strip foundation resting on a homogenous elastic half-space. The developed impedance functions are then used in an extensive parametric study analyzing the changes of the fundamental frequency of bridge piers for different combinations of the geometrical and mechanical properties of the soil-structure-foundation system. The study results shed light on the effects of scour on the dynamic properties and fundamental frequency of vibration of bridges with shallow foundations and have important implications on the development of inverse techniques for scour identification based on the evaluation of the changes in the bridge modal properties. Highlights: Scour affects differently the various components of the dynamic impedance of shallow foundations. Linear reduction of the fundamental vibration frequency for increasing scour widths. Effects of scour on fundamental period elongation are more significant for stiff but tall piers on soft soils.